The Effect Risk of Credit, Efficiency, and GCG of Bank Profitability (Study in Conventional Commercial Banks Registered on the Indonesia Stock Exchange Period 2012 - 2019) - Ayuningrum, Anggrainy Putri (Universitas Negeri Semarang, 2021)
The purpose of this study to test the effect of risk credit, efficiency and Good Corporate Governance to profit bank in the Indonesian conventional bank. GCG represented by board size, board meeting and disclosure. This study used quantitive research using purposive sampling method and obtained 22 banks by the annual bank report of BEI during 2012-2019 were selected as samples with a total of 174 observation. Data analysis in this study is a multiple linear regression analysis using SPSS Statistic 22. This study is NPL, and BOPO has a negative and significant effect on conventional commecial bank’s profitability. The control variable has size get a positive and significant impact to profitability bank. Board Size, Board Meeting, and Disclosure have not significant effect to the profitability bank. The advice provide is bank should pay attention to risk mitigation of credit and do efficiency on their activity. Furthermore, researchers are also expected to add other independent variables that can affect profitability banks such as CAR, LDR , Risk Commite Meeting, and other control variables like age.